Indigofera pseudonigrescens (Fabaceae: Papilionoideae): A new species from Sichuan, China - Zhao, Xue-Li; Gao, Xin-Fen (Phytotaxa, 2015)
Indigofera pseudonigrescens (Fabaceae), a new species from Sichuan, China, is described and illustrated based on morphological and molecular evidence. The new species is morphologically similar to I. nigrescens, but differs from the latter in having shorter bracts, smaller leaflet size, and fewer leaflets whose abaxial surfaces do not become dark or black or do not have black spots when dry. Molecular analysis based on nuclear (nrITS) and plastid (ndhJ-trnF, atpF-atpH) data indicated that I. pseudonigrescens is clearly distant from I. nigrescens. The results also revealed that I. pseudonigrescens is phylogenetically close to I. delavayi which is morphologically remarkably different from I. pseudonigrescens.